Analisis Kesulitan Membaca Permulaan Di Kelas IV SDN Jatinegara Kaum 14 Pagi - Novianti Novianti; Yosua Sebastian; Zanatin Naim Al Islami; Indra Jaya; Rohmah Ageng Mursita (Journal of Creative Student Research, 2024)
The main problem in this research is the lack of students’ initial reading abilities, so it is necessary to analyze the difficulties that influence students’ initial reading abilities. This research aims to identify and understand the factors that hinder the beginning reading abilities of fourth grade students.The type of research used in this study is qualitative with instruments in the form of observation, interviews, and documentation regarding beginning reading. The data obtained was analyzed using data analysis techniques, namely data reduction, data presentation, and drawing conclusions to test the validity of the data. The results of the research that have been described are initial reading difficulties in fourth grade elementary school students who are not able to differentiate between letters that have almost the same shape, are not able to read combinations of consonants and are not able to read consonants and vowels. The conclusion of this research is that difficulties in beginning reading are due to the student’s lack of interest in learning, lack of interest in reading, lack of study guidance and lack of family assistance in the process of learning to read at the beginning as well as factors within the student. The implication of carrying out this research is to motivate students to be more confident in expressing opinions, motivating them to be more active in learning to read at first.